Avaliação in vitro da rugosidade e do desgaste dentinário após escovação com dentifrícios clareadores - Tahim, Catarina Martins (2014)
The aim of this study was to compare the mechanical profilometry the abrasive effect of toothbrushing on root dentin with bleanching and conventional toothpastes. Ninety -six blocks of bovine root dentin (10x4x2 mm) were randomly divided into six experimental groups (n= 16) according to the dentifrices: four bleaching (W1, W2, W3 and W4) and two not bleaching (C1 and C2), produced by two different manufacturers. Using a brushing machine, each block was brushed with a constant load of 300 g for 2500 cycles (4.5 movements per second). The dentifrices were diluted in a 1:3 ratio by weight (Dentifrice/ remineralizing solution). The samples were evaluated by mechanical profilometry. The diamond tip of the profilometer moved at a constant speed of 0.05 mm/s with a force of 0.7 mN. The average readings of the wear and resulting surface roughness was obtained brushing five consecutive readings in each specimen. To wear in micrometers (μm): W1= 3,91±1,55; W2= 2,19±1,04; W3= 2,80±1,63; W4=1,41±0,69 ; C1= 1,42±0,71; C2= 0,86±0,33 and for roughness in micrometers (μm): W1= 0,70±0,46; W2= 0,32±0,21; W3= 0,49±0,26; W4= 0,23±0,11; C1= 0,20±0,08; C2= 0,13±0,04. There were significant differences between groups for both wear and surface roughness (ANOVA - P < 0.0001). Among the groups, it was observed that the W1 group showed higher roughness and wear, which was statistically different from all others. The W1 toothpaste along with toothpaste W3 showed differences from conventional toothpastes and W4. Among these differences were not observed. On the other hand, the whitening dentifrice W2 showed intermediate values being different from W1 and C2. A whitening toothpaste showed greater harmful potential with respect to wear and roughness of the others. Whitening dentifrices resulted in greater wear and a greater surface roughness than conventional dentifrices.